Trichoderma spp.-mediated mitigation of heat, drought, and their combination on the Arabidopsis thaliana holobiont: a metabolomics and metabarcoding approach - Senizza, Biancamaria; Araniti, Fabrizio; Lewin, Simon; Wende, Sonja; Kolb, Steffen; Lucini, Luigi (Frontiers in Plant Science, 2023)
The use of substances to increase productivity and resource use efficiency is now essential to face the challenge of feeding the rising global population with the less environmental impact on the ecosystems. Trichoderma-based products have been used as biopesticides, to inhibit pathogenic microorganisms, and as biostimulants for crop growth, nutrient uptake promotion, and resistance to abiotic stresses. In this work, plant metabolomics combined with roots and rhizosphere bacterial metabarcoding were exploited to inspect the performance of Trichoderma spp. biostimulants on Arabidopsis thaliana under drought, heat and their combination and its impact on plant holobiont. An overall modulation of Ncontaining compounds, phenylpropanoids, terpenes and hormones could be pointed out by metabolomics. Moreover, metabarcoding outlined an impact on alpha and beta-diversity with an abundance of Proteobacteria, Pseudomonadales, Burkholderiales, Enterobacteriales and Azospirillales. A holobiont approach was applied as an integrated analytical strategy to resolve the coordinated and complex dynamic interactions between the plant and its rhizosphere bacteria using Arabidopsis thaliana as a model host species.